Case report of malignant peripheral nerve sheath tumor of parotid in a patient with neurofibromatosis type 1 - P., Anuradha; Reddy, Bathi; Gaur, Suhail (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Malignant peripheral nerve sheath tumor (MPNST) refers to spindle cell sarcomas arising from or separating in the direction of cells of the peripheral nerve sheath. The MPNST of the parotid gland is an extremely rare tumor, accounts for <5% of all soft tissue sarcomas, and carries a poor prognosis. Diagnosis of MPNSTs is usually based on histopathology aided by IHC, which reflects the Schwann cell differentiation in this neoplasm. Approximately 50-90% of MPNSTs are positive for S-100 protein. A 56-year-old male presented with right parotid swelling for 3 months and incomplete right eye closure. The patient was diagnosed with neurofibromatosis 1 (NF-1) and pulmonary tuberculosis in the past. On Examination, a hard, tender swelling measuring 5×4 cm involving the right parotid gland and right grade 2 LMN facial palsy was noted. Histopathology was suggestive of a MPNST.